Semiquantification of volatile compounds and identification of potential volatile markers and dry aroma from robusta second-crack roasted coffee processed from several post-harvest processing - Nur Fajriani Suaib; Didah Nur Faridah; Dede Robiatul Adawiyah; Nuri Andarwulan (AIMS Agriculture and Food)
In Bogor, the farmers employed several methods for robusta post-harvest processing, including natural, honey, full wash, and wine processing. This research was conducted to examine the influence of the different post-harvest processing methods on volatile compounds and to identify volatile markers that can authenticate coffee roasted under second-crack roasting and characterize its dry aroma. The study identified and semiquantified 140 compounds. Post-harvest processing affected carboxylic acids, esters, alcohols, hydrocarbons, phenolics, thiophenes, and total volatile compounds. Principal component analysis (PCA) modeling showed that natural and honey processes had similar volatile compound compositions, while full wash and wine processes tended to differ. Based on the variable importance in projection (VIP) values from orthogonal partial least square discriminant analysis (OPLS-DA) modeling and percent contribution, two compounds (i.e., ethyl salicylate and 2-Methyl-5-methoxy-4H-pyran-4-one) were identified as potential markers for natural and wine processing. Ethyl acetate and 5-amino-2-methylbenzothiazole were identified as potential markers for wine processing. Honey and full wash processing did not have any distinct volatile marker. Natural processing exhibited a dry aroma of caramelly, roasted peanut, and chocolate, while honey processing had caramelly, nutty, and earthy aromas. Full wash processing had sweet nut, earthy, and herbal aromas with a hint of potato, and wine processing had fermented, winey, molasses, and chocolaty aromas. This research demonstrated that post-harvest processing influenced volatile compounds in second-crack roasted coffee. Identifying potential markers provides valuable information for authenticating second-crack roasted coffee and differentiating it based on post-harvest processing and dry aroma.